IMPLEMENTASI CUSTOMER RELATIONSHIP MANAGEMENT (CRM) PADA CV PUSTIKOM BERBASIS WEB DAN SMS - Fahmi Yusuf; Erik Kurniadi; Akmal Sumirat (NUANSA INFORMATIKA, 2011)
CV Pustikom is a company that engaged in the sales and service by utilizing Information Technology (IT). The use of Information Technology (IT) become a fundamental necessity in the face of competition in the Information Age. To retain customers, the company used information technology systems such as Customer Relationship Management (CRM) is a facility system used to maintain and organize the customer in order to remain confident and loyal to the company. The usege and Implementation CRM in the enterprise can improve services, obtain customer data and provide information to customers in order to serve the customer in purchasing the company’s products, increased promotion, and publicity firm. With the application develop a website that allows access anywhere and anytime and SMS support has been more and more use, then using a waterfall system development methods and approaches Data Flow Diagram (DFD) as a system design tool. The writer used the implementation of CRM by using the application form SMS as a service website and purchase the company’s products and provide informaton to customers.  Keywords:   Customers, CRM, WEB, SMS